THE INFLUENCE OF BLOOD RHEOLOGY IN SIMULATING BLOOD FLOW ON BRAIN ARTERY WITH ANEURYSM - ,, MUHAMADYUNUS (2014)
Cerebrovascular disease is a term related to disorder in brain blood vessels, which abnormalities due to disorder of blood flow in brain vessel is a major cause of stroke that leads to death. The implication could leads include to stroke and ischaemic attack. Stroke caused by destruction of brain cells due to blood supply reduction. Impairment of sight as well as inability to speak, taste and move is a typical ischaemic attack symptoms. Aneurysm is a condition in diseased artery where the bulging artery will rupture and caused severe bleeding in brain. An aneurysm is formed when a blood vessel becomes dilated or distorted causing the vessel to expand to a size greater than its original diameter. Aneurysms can occur in a variety of blood vessels though they are most commonly found in the intracranial arteries.